LATERAL MARKETING AS INSTRUMENT OF CREATION OF NEW COMMODITY CATEGORY - N. Zemlyanskaya; N. Kazakova (Вестник университета)
The concept of lateral marketing as the system of nonconventional methods of advance of goods and services allowing to fight successfully against the competition is considered. The structure of lateral marketing consisting of four steps is given: focus choice, level choice, generation of a marketing gap and establishment of communication or elimination of a gap. New application of a product or creation of new market category can become the end result of lateral marketing.